Technological Proposal of Conciliation Application and Dispute Settlement - Pantoja, Emillyn Bárbara Assunção (2019)
Conciliation is an alternative means of conflict resolution in which the parties settle their dispute through an agreement in which they will meet their wishes. Thus, in conciliation there are no winners and no losers. The objective of the present work was to perform technological prospection, scope analysis and the characteristics of patents related to conciliation application. For this, the databases of the National Institute of Intellectual Property (INPI) and the European Patent Office (ESPACENET). The results obtained indicate that the majority of patent applications related to the conciliation application facilitating the agreement between the parties was in 2002 with five filings, and the country with the largest number of filings was the United States. In Brazil it is verified that the theme is little explored.